Do inquiry-based teaching and school climate influence science achievement and critical thinking? Evidence from PISA 2015 - Ricardo L. Gómez; Ana María Suárez (International Journal of STEM Education, 2020)
Abstract Background Inquiry-based teaching (IBT) and improving school climate are the two most commonly used strategies for fostering learning and critical thinking skills in students. IBT has positioned itself as one of the most recommended “active” methodologies for developing intellectual autonomy and complex thought processes, whereas school climate is considered to be a protective factor that helps mitigate adverse conditions and has a positive impact on teaching and learning. This study investigates the relationship between IBT and school climate with the academic performance of Colombian students in the PISA 2015 test. Results Using a two-level Hierarchical Linear Modeling (HLM), the results show a negative association between IBT and students’ scientific performance in the test. However, results show a positive association between IBT and students’ self-reported critical thinking skills. Results also show that school climate is a positive moderating factor on learning. Contextual factors such as the student’s grade level at the time of sitting for the PISA test, gender, and socioeconomic characteristics are strong predictors of science achievement in PISA. Conclusions These results reveal the need for additional research on the effect of the so-called active methodologies and school context on student learning. Regarding IBT, it seems that its influence is greater on student’s perception and motivation, than in acquisition of scientific knowledge. Positive school climate is a protective factor that can help to improve student learning. In Colombia, the quality of students’ educational outcomes has largely been attributed to their socioeconomic background. However, the results of this study show that, although students’ and schools’ socioeconomic characteristics continue to be strong predictors of academic performance, teaching practices can have an even larger impact.